Aplikasi Monitoring Server dan Analisis Kualitas Menggunakan Model ISO 9126 - Triyadi Triyadi (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
Server’s role is very important. However, in reality, server does not run well because there are always disruption or disturbance in its hardware and software, requiring special and prompt handling them. The purpose of this research is to produce a server monitoring software by testing the quality of the software based on the standard ISO/IEC 9126 on the aspects of functionality, efficiency, reliability, and usability. The research uses a Research and Development (R&D) method with the development model of Rapid Application Development (RAD) consisting of Planning terms, Workshop Design and Implementation Phase. The result of test on the server monitoring application show that the functionality score is in a good category or fulfills the aspects of functionality and the test on aspects of efficiency using YSlow results in Grade A. The test on aspects of reliability using WAPT 8.5 reliability shows that the reliability score is in a good category or fulfills the aspects of reliability and the test on aspects of usability results in a good category.